Strategi Peningkatan Kompetensi SDM Aparat Pemerintahan Dalam Menjawab Tantangan Masyarakat Ekonomi ASEAN (MEA) - Widodo, Erna (Jurnal Wahana Bina Pemerintahan, 2016)
The ability to plan and manage change of a goverment adminstrative policies and the substance of macro, micro and central demand in MEA era. The authorities demanded to be able to accept change as a characteristic of life, to understand the consequences for changes. The apparatus in accordance with the conditions of globalization is the apparatus capable of commanding and controlling changes in sound sciene and technology. Accomodates a variety of changes in sciene and technology be used as food for thought fo the goverment and training. Refering to the progress of a country deciding factor, namely; mastery of innovation (45% 0, control network/networking (25%O, mastery of technology (20%) and a wealth of natural resources only (10%), the increase in the professionalism of officers should be increased as wll as the role of the goverment in resolving the problem of goverment especially the challenges facing the MEA in the future, one of them with the allocated budget for education and training of goverment adequate acompanied by supervision of the implementation of the budget would have to be used to improve the professionalism of officials and geverments in Indonesia and is expected also to be able to bring Indonesia to the gates of success toward the Asean Economic Community (AEC)